2018
DOI: 10.1007/s40831-018-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation Resistance of Alkali-Activated Slag Under Natural and Accelerated Conditions

Abstract: In this paper, carbonation resistance of alkali-activated slag (AAS) pastes exposed to natural and accelerated conditions up to 1 year was investigated. Two aspects of carbonation mechanism were evaluated. The first was the potential carbonation of the main binding phases in finely powdered AAS pastes. The second was the reactivity and diffusivity of CO 2 within the bulk AAS paste. From Fourier transform infrared spectroscopy and thermogravimetric analysis coupled with mass spectroscopy time-series measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…These are indirectly supported by the previous study of the authors where it was shown that paste S100 has a different compressive strength development in sealed and unsealed curing conditions [42].…”
Section: Carbonation Depthsupporting
confidence: 78%
“…These are indirectly supported by the previous study of the authors where it was shown that paste S100 has a different compressive strength development in sealed and unsealed curing conditions [42].…”
Section: Carbonation Depthsupporting
confidence: 78%
“…Figure 7 shows the decomposition temperature of hydrates and carbonates in TG/DTG [ 32 ]. Figure 8 , Figure 9 and Figure 10 show the TG/DTG results for accelerated carbonation of each specimen.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the BFS/FA blend, it is known that C–(N)–A–S–H and N–A–S–H gels are formed simultaneously; hence, it can be assumed that not only the Na + concentration but also the structure of the gel formed due to the type of binder would affect the crystallinity of the CaCO 3 produced under accelerated carbonation conditions. From the results of the F100 sample shown in Figure 10 , the difference between the decomposition amounts of 100–200 °C at high and low levels of Na + concentration is confirmed [ 32 ]; this difference is considered to depend on the degree of formation of the N–A–S–H gel. In addition, the decomposition from sodium bicarbonate or sodium carbonate is slightly increased owing to the overall carbonation level, and this increase is remarkable in specimens with high Na + concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…e noncarbonated samples show weak peak at 3640 cm − 1 , which corresponds to H-O stretching vibrations of Ca(OH) 2 . e peak near 950 cm − 1 corresponds to the Q 2 vibration of the v 2 Si-O bond in the hydrate product-C-S-H [32,33]. e calcium carbonate formed by the reaction of the powdered specimen with CO 2 in air is also reflected in the FT-IR spectra.…”
Section: Ft-ir Analysismentioning
confidence: 99%